A cross-spectral target tracking method based on a hidden Markov model. Issue 1 (1st January 2023) - Wang, Liming; Su, Peilin; Huang, Di
Abstract: Aiming at the problem of target tracking stability in the case of low signal-to-noise ratio and multi-target cross-motion, this paper combines the hidden Markov model and complementary tracking and proposes a new automatic tracking method. The stability of the new algorithm is proved by theoretical analysis and computer simulation experiments. In the case of low signal-of-noise ratio and multi-target cross-motion, the new algorithm has good performance.